2018
DOI: 10.1007/s10936-018-9598-z
|View full text |Cite
|
Sign up to set email alerts
|

The Processing of Grammatical Gender Agreement in Brazilian Portuguese: ERP Evidence in Favor of a Single Route

Abstract: The present study used event-related potentials to investigate whether the processing of grammatical gender agreement involving gender regular and irregular forms recruit the same or distinct neurocognitive mechanisms and whether different grammatical gender agreement conditions elicit the same or diverse ERP signals. Native speakers of Brazilian Portuguese read sentences containing congruent and incongruent grammatical gender agreement between a determiner and a regular or an irregular form (condition 1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…They have also found a higher accuracy for transparent vs. opaque nouns, which lead to the conclusion that gender transparency facilitates noun recognition. Similar results were obtained in a study with Portuguese-speaking adults, which revealed that gender errors are more easily detected between a transparent noun and a determiner than between an opaque noun and its determiner (Alencar de Resende, Mota & Seuren, 2018).…”
Section: Gender Processing Studies In Adultssupporting
confidence: 83%
“…They have also found a higher accuracy for transparent vs. opaque nouns, which lead to the conclusion that gender transparency facilitates noun recognition. Similar results were obtained in a study with Portuguese-speaking adults, which revealed that gender errors are more easily detected between a transparent noun and a determiner than between an opaque noun and its determiner (Alencar de Resende, Mota & Seuren, 2018).…”
Section: Gender Processing Studies In Adultssupporting
confidence: 83%